Genetic Relationship and Selection Indices of Nine Irradiated Quantitative Traits of F1 Materials in lentils (Lens Culinaris Medic.) - Deb, Anil Chandra; Chowdhury , Anuradha Roy (Jordan Journal of Agricultural Sciences, 2022)
F1 materials of half-diallel crosses for nine characters in lentils were studied for correlation, path-coefficient, and selection index. The phenotypic component of variation (σ2p) was higher than the genotypic component of variation (σ2g). The highest σ2g and σ2pwere obtained for CAMF. Investigation showed that genotypic correlations (rg) were higher than the respective phenotypic correlations (rp) for most of the characters. SWPP showed a highly significant and positive correlation coefficient with other characters except for the NPBFF at the genotypic level and except NPBFF and DF at the phenotypic level. The highest significant and positive genotypic correlation coefficient was recorded for NSBFF with PdWPP at the genotypic level and PdWPP with SWPP at the phenotypic level. PdWPP had the highest positive direct effect on SWPP at both genotypic and phenotypic levels. The maximum expected genetic gain of 4603.196% was found when NPBFF and RW were included in the index. These two characters a had high correlation coefficient with most of the characters studied as well as a direct effect at the genotypic level may be considered as primary yield components.